Growth and Characterization of Vertical and Lateral p‐n Junctions Formed by Selective‐Area p‐GaN MOVPE on Patterned Templates. Issue 2 (25th November 2018) - Debald, Arne; Kotzea, Simon; Heuken, Michael; Kalisch, Holger; Vescan, Andrei
Abstract : In this work, vertical and lateral GaN p‐n junctions are investigated. In particular, there is a strong demand of lateral p‐n junctions for the realization of numerous types of power devices. The comparison of I‐V characteristics of regrown and continuously‐grown p‐n diodes, formed by metal‐organic vapor phase epitaxy (MOVPE), reveals the impact of different surface treatments before regrowth. The use of tetramethylammonium hydroxide (TMAH) prove vital for growth on etch‐damaged GaN and to smoothen vertical sidewalls for selective‐area regrowth (SAR). Initial growth on patterned templates is identified to occur both vertically on the horizontal c‐plane and laterally on the vertical m‐planes allowing for an integration of the developed process in power device fabrication routes. The formation of local superelevations (LSE) near edges of masked areas is analyzed and explained. Abstract : In this article, vertical and lateral p‐n junctions are fabricated utilizing metal‐organic vapor phase epitaxy (MOVPE) selective‐area regrowth. Lateral p‐n junctions are a key component for a variety of power devices, e.g., junction barrier Schottky diodes (JBSDs), edge termination, current shaping in vertical transistors like current aperture vertical electron transistor (CAVET), and gate diodes in vertical junction field effect transistors (vJFETs).